2017
DOI: 10.1007/s40263-017-0433-0
|View full text |Cite|
|
Sign up to set email alerts
|

Pregnancy Outcomes Following In Utero Exposure to Lamotrigine: A Systematic Review and Meta-Analysis

Abstract: No association was found between prenatal lamotrigine monotherapy and increased rates of birth defects and other explored variables related to adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 61 publications
1
29
0
1
Order By: Relevance
“…In 2009, an increased risk of cleft palate and lip was reported after an exposure during the first trimester of pregnancy . However, this risk was not confirmed by other studies …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In 2009, an increased risk of cleft palate and lip was reported after an exposure during the first trimester of pregnancy . However, this risk was not confirmed by other studies …”
Section: Discussionmentioning
confidence: 93%
“…38 However, this risk was not confirmed by other studies. 39 During the first years of the study period, carbamazepine was the most frequently prescribed AED in Emilia Romagna, with more than 20% of pregnant women exposed to AEDs receiving carbamazepine.…”
Section: Drug Choice Differs According To Countriesmentioning
confidence: 99%
“…Of utmost importance, the risk of major congenital malformations among children who were exposed to LTG appears null in a prospective registry of 18 years . In addition, among 96 studies including 58,461 individuals, the risk observed under LTG did not differ from that reported in healthy individuals in contrast with findings obtained with most other antiepileptic drugs . Moreover, a large prospective cohort study shows that fetal exposure to LTG does not affect IQ or any detectable neuropsychological ability in children up to 6 years of age .…”
Section: The Safety and Tolerance Of Lamotrigine Appears Among The Himentioning
confidence: 64%
“…In comparisons of women exposed to lamotrigine with those unexposed, published studies reported null or adverse effects on pregnancy duration and birth weight [14,20,23], protective or null effects on SGA [14,20,24], and null effects on head circumference [13,20]. A recent systematic review that focused on lamotrigine concluded that there was no association between lamotrigine in monotherapy and congenital malformations, preterm delivery, or SGA [28,29]; but a dose dependency was reported for congenital malformations. [5].…”
Section: Lamotriginementioning
confidence: 99%
“…Overview 90 We conducted a cohort study based on nationwide Swedish register data from 1996 through 2013 91 to explore the association between maternal use of individual AEDs and pregnancy duration and 92 fetal size. Lamotrigine was the reference AED because it is commonly used and has been 93 considered to have fewer adverse fetal effects than other AEDs [2,12,28,29]. 94 Data sources 95 In Sweden, tax-funded health care is provided to all citizens.…”
mentioning
confidence: 99%